New Directions in Wireless Communications Research - Tarokh, Vahid (Springer US : Imprint: Springer, 2009)
New Directions in Wireless Communications Research addresses critical issues in the design and performance analysis of current and future wireless system design. Intended for use by system designers and academic researchers, the contributions are by acknowledged international leaders in their field. Topics covered include: Characterization of wireless channels The principles and challenges of OFDM Low-correlation sequences for communications Resource allocation in wireless systems Signal processing for wireless systems, including iterative systems collaborative beamforming and interference rejection and network coding Multi-user and multiple input-multiple output (MIMO) communications Cooperative wireless networks, cognitive radio systems and coded bidirectional relaying in wireless networks Fourth generation standards such as LTE and WiMax and standard proposals such as UMB The volume will be an indispensable reference for all workers in the area of wireless system design.